INOVASI PRODUKTIVITAS PAVING BLOCK MELALUI ALAT PLASTIK MELTER DI BUMK DESA REMBUNE, BENER MERIAH - Muhammad; Reza Putra; Muhammad; Teuku Hafli; Asnawi; Nurul Islami; Nur Azura Lubis; Azi Maulana Ikbal; Fadhil Risky Ramadhana; Ali Nur Muhammad Zaidin Balatif (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
English, Rembune Village, one of the communities with very interesting tourist potential, located in Timang Gajah District, Bener Meriah Regency. However, the residents of Rembune Village deal with several issues, one of which being the abundance of plastic waste around. The community uses the BUMK Rembune Village to transform plastic trash into paving blocks in order to solve the problem of mountains of plastic waste. In this instance, BUMK Rembune Village and the Community Empowerment Service (PPM) team from the Faculty of Engineering at Malikussaleh University conduct a program to improve knowledge and skills for the community. The solution offered involves transferring technology for a plastic melter tool to the community through partners. Furthermore, the PPM team provided training at the partner locations on how to manage and process plastic waste as well as technology transfer for plastic melter equipment. The competence of community organizations or partners to convert plastic garbage into paving blocks that can reduce the issue of plastic waste in Rembune Village is an indicator for the performance of this PPM activity. Additionally, the plastic melter machines that have been distributed to community organizations and partners may be operated and maintained by them. Activities for the Community Empowerment Service (PPM) at the Rembune Village have been progressing as planned, and therefore, partners may boost the productivity of their businesses and serve as motivation for other community organizations Bahasa, Desa Rembune berada di Kecamatan Timang Gajah, Kabupaten Bener Meriah yang merupakan salah satu desa dengan potensi wisata yang sangat menarik. Namun terdapat beberapa masalah yang dialami oleh masyarakat Desa Rembune salah satunya adalah banyaknya timbunan sampah plastik pada kawasan tersebut. Untuk mengurai permasalahan timbunan limbah plastik tersebut, maka masyarakat melalui BUMK Desa Rembune melakukan pengolahan limbah plastik menjadi paving block. Dalam hal ini tim Pengabdian Pemberdayaan Masyarakat (PPM) Fakultas Teknik Universitas Malikussaleh memberikan program peningkatan pengetahuan dan keterampilan bagi masyarakat dan mitra pelaksana yaitu BUMK Desa Rembune. Metode yang ditawarkan adalah alih teknologi alat melter plastik yang diserahkan kepada masyarakat melalui mitra. Selanjutnya, di lokasi mitra tim PPM melaksanakan edukasi tentang manajemen pengolahan sampah plastik dan alih teknologi mesin melter plastik serta cara perawatannya. Indikator capaian kegiatan PPM ini, Kelompok Masyarakat atau mitra telah mampu mengolah limbah plastik menjadi paving block yang dapat membantu dalam mengurangi permasalahn limbah plastik di Desa Rembune. Selain itu, kelompok masrakat dan mitra juga mampu mengoperasikan dan me-maintenance mesin melter plastik yang telah diserah terimakan kepada kelompok masyarakat/ mitra tersebut. Kegiatan Pengabdian Pemberdayaan Masyarakat (PPM) pada BUMK Desa Rembune telah berjalan sesuai perencanaan, berikutnnya mitra dapat meningkatkan produktivitas usahanya dan bertranformasi sebagai motivator bagi kelompok masyarakat lain.